Fast-Growing Meningioma in a Woman Undergoing Fertility Treatments. (26th December 2016) - Patterson, Adam; Elashaal, Abdurrahim
Abstract : Meningiomas have long been known to be associated with sexual hormones. We discuss here the case of a woman with a huge meningioma that rapidly grew over the course of a couple years while the patient was simultaneously taking fertility treatments. There is substantial evidence suggesting that fertility treatments can fuel the growth of meningiomas. The potential risks should be considered in women with a previous or family history of meningiomas who plan to undergo fertility treatment. These patients need to be evaluated and a screening imaging of brain MRI (Magnetic Resonant Imaging) should be offered in the middle or toward the end of such a treatment to control and prevent complications of these meningiomas.